Xanthelasma palpebrarum – a brief review - Nair PA; Singhal R (Dove Medical Press, 2017)
Pragya A Nair, Rochit Singhal Department of Dermatology, Venereology and Leprosy, Pramukhswami Medical College, Gujarat, India Abstract: Xanthelasma palpebrarum is the most common cutaneous xanthoma, characterized by yellowish plaques over eyelids – most commonly, over the inner canthus of the upper lid. It is triggered by hyperlipidemia, thyroid dysfunction, and diabetes mellitus. Xanthelasma results from perivascular infiltration of mono- and multinucleated foam cells within lipid-laden cytoplasmic vacuoles in the superficial reticular dermis. Different modalities of treatment, such as simple surgical excision, cryotherapy, chemical peeling with trichloroacetic acid, radiofrequency, and laser, are used in the treatment of xanthelasma palpebrarum. A brief review of current treatment strategies is presented here. Keywords: xanthelasma palpebrarum, xanthoma, hyperlipidemia, laser, cryotherapy